2010
DOI: 10.1057/jit.2010.6
|View full text |Cite
|
Sign up to set email alerts
|

Online Social Networks: Why We Disclose

Abstract: On online social networks such as Facebook, massive self-disclosure by users has attracted the attention of Industry players and policymakers worldwide. Despite the Impressive scope of this phenomenon, very little Is understood about what motivates users to disclose personal Information. Integrating focus group results Into a theoretical privacy calculus framework, we develop and empirically test a Structural Equation Model of self-disclosure with 259 subjects. We find that users are primarily motivated to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
694
5
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 779 publications
(744 citation statements)
references
References 48 publications
32
694
5
13
Order By: Relevance
“…Krasnova et al 2010a Drawing from the works presented above, we describe Perceived Privacy Risk as the degree to which a person believes that using an SNS has negative consequences with regards to his/her privacy (cf. Chen 2013; Dinev and Hart 2006;Featherman and Pavlou 2003;Kim et al 2008;Krasnova et al 2010b;Peter and Ryan 1976;Wu et al 2009). …”
Section: Definitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Krasnova et al 2010a Drawing from the works presented above, we describe Perceived Privacy Risk as the degree to which a person believes that using an SNS has negative consequences with regards to his/her privacy (cf. Chen 2013; Dinev and Hart 2006;Featherman and Pavlou 2003;Kim et al 2008;Krasnova et al 2010b;Peter and Ryan 1976;Wu et al 2009). …”
Section: Definitionmentioning
confidence: 99%
“…Indeed, multiple studies have confirmed a negative influence of Perceived Privacy Risk on SNS members' information disclosure behavior. For example, Lo (2010) found that Perceived Privacy Risk negatively influences the general Willingness to provide personal information to SNSs; Krasnova et al (2010b) found that it has a negative influence on the actual amount of self-disclosed information.…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Krasnova et al (2009) in their study reported that commercial agents or marketers target message to specific interest groups the same way through search engine or traditional advertising channels. The other way of reaching consumers is for brands, setting up their profiles on Social Networking Sites, accepting "friends" they can keep up to date with the latest brands.…”
Section: Marketing On Online Social Network (Osn)mentioning
confidence: 99%